Pengembangan Pariwisata Berwawasan Lingkungan di Nagari Sungai Pinang, Kecamatan Koto XI Tarusan, Kabupaten Pesisir Selatan - Wahyu Pramono; Indraddin Indraddin; Faidil Tanjung (Warta Pengabdian Andalas, 2021)
Nagari Sungai Pinang is a village with quite a lot of tourism potential and an excellent and exciting view and natural beauty. For this reason, various sector reinforcement is necessary to support the development of tourism potential by formulating a program of tourism development activities that are environmentally sound. The purpose of this activity was to improve the quality of tourism in the Nagari, namely Nagari Sungai Pinang, to increase the economic income of the community and the village itself. At the same time, the purpose of the activity was to facilitate Nagari in developing environmentally friendly tourism businesses by compiling a five-year tourism development program in Nagari Sungai Pinang. The methods used to carry out this activity were Desk Study and Transect Walk, observation, focus group discussion and data analysis. The trial activities were carried out in Nagari Sungai Pinang, Koto XI Tarusan District, Pesisir Selatan Regency. The activity results were in an activity program for tourism development for five years in Nagari Sungai Pinang. The tourism development strategy is held by empowering tourism actors and involved stakeholders. Moreover, achieve the sustainability of the program. Good planning is carried out in a participatory manner involving various elements to build a sense of belonging to various parties and realize program sustainability.